2013
DOI: 10.1002/cmdc.201300362
|View full text |Cite
|
Sign up to set email alerts
|

PET Radiotracers for Imaging P‐glycoprotein: The Challenge for Early Diagnosis in AD

Abstract: PET radiotracer development to target in vivo P-glycoprotein (P-gp) could be an important strategy for the early diagnosis of neurodegenerative disorders such as Alzheimer's disease (AD). Indeed, as a dysfunction of P-gp is responsible for the accumulation of β-amyloid plaques (a hallmark of AD) in brain parenchyma, P-gp is the cause of AD onset. P-gp substrates and inhibitors are useful for imaging the activity or expression of this protein, respectively; herein we discuss the in vivo evaluation of some ¹¹C r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In all of the designed series, the choice of substituents was evaluated for the additional purpose of generating useful tools with easy radiolabeling points, such as a methoxy group or fluorine, for in vivo PET ( 11 C or 18 F) analysis to monitor P-gp activity and expression. …”
Section: Introductionmentioning
confidence: 99%
“…In all of the designed series, the choice of substituents was evaluated for the additional purpose of generating useful tools with easy radiolabeling points, such as a methoxy group or fluorine, for in vivo PET ( 11 C or 18 F) analysis to monitor P-gp activity and expression. …”
Section: Introductionmentioning
confidence: 99%
“…While these aspects above were mostly relevant for therapeutic drug development, the discovery of inhibitors of ABCA7 by addressing the multitarget binding site and their simultaneous derivatization to selective agents would allow for in vivo imaging of ABCA7. Imaging of ABC transporters of the BBB has already been accomplished before [63] , and the results of the present study found the basis for PET tracer development of other, yet under-studied ABC transporters involved in neurological disorders like AD, as for example, ABCA7.…”
Section: Discussionmentioning
confidence: 69%
“…Additionally, it must be noted that several activators of ABC transporters share molecular-structural features of ABC transporter inhibitors. For example, tetrahydroisoquinolines (ABCB1) [48] , [62] , [63] and pyrrolopyrimidines (ABCC1) [49] , [64] have been described for both activators [48] , [49] and inhibitors [62] , [63] , [64] of ABCB1 and ABCC1, respectively. Other examples are the compound classes of phenothiazines [65] , [66] and purines [49] , [67] , [68] , which have been described to comprise of ABCC1 activators [49] , [65] , [66] and ABCB1 inhibitors [65] , [66] , [67] , [68] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, these results increase our knowledge of the structural determinants for obtaining potent and selective P‐gp substrates or P‐gp inhibitors. These compounds could also be promising candidates as 11 C radiolabeled tracers for in vivo positron emission tomography (PET) imaging, as P‐gp substrates and inhibitors are useful for visualizing P‐gp activity and for the early detection of the in vivo expression of this pump in tumor cells, respectively 30…”
Section: Methodsmentioning
confidence: 99%